Chain-Branched Polyhydroxylated Octahydro-1H-Indoles as Potential Leads against Lysosomal Storage Diseases - Juan C. Estévez; Marcos A. González; M. Carmen Villaverde; Yuki Hirokami; Atsushi Kato; Fredy Sussman; David Reza; Ramón J. Estévez (MDPI AG, 2019)
Here, the synthesis and glycosidase inhibition properties of the two first known 3-ethyloctahydro-1H-indole-4,5,6-triols are reported. This study shows the transformation of d-glucose into polyhydroxylated 1-(2-nitrocyclohexane) acetaldehydes, followed by a protocol involving the formation of the azacyclopentane ring. Results of inhibitory potency assays and docking calculations show that at least one of them could be a lead for optimization in the search for compounds that behave like folding chaperones in lysosomal storage diseases.